ANALISIS KOMPOSISI UNSUR DAN JENIS MINERAL BATUAN GUNUNGAPI SOPUTAN MENGGUNAKAN SEM-EDX DAN FTIR - Yosua Walewangko; Cyrke A. N. Bujung; Jeane Cornelda Rende (Jurnal FisTa : Fisika dan Terapannya, 2021)
Volcanoes are mountains that are formed as a result of eruption material accumulating around the center of an eruption or a mountain formed from a magma eruption. Volcanoes are only found in certain places, namely in the mid-ocean ridge, at the point where two plates of the Earth's crust meet, and at hot spots on the earth where magma is released, on continents and in oceans. Indonesia is a country with active volcanoes formed due to subduction zones between three tectonic plates, namely the Eurasian plate, the Indo-Australian plate and the Pacific plate. The location of the research was carried out in the Soputan Volcano Area, by taking two samples, namely two different rock types in the study area. This study aims to determine the elemental composition of the rock and rock mineral types in Soputan Volcano. Using SEM-EDX and FTIR. The results of the research on sample 1 of the EDX device were Bromine, Silica, Tungstate, Gold, Molybdenum, Calcium, Iron, Iterbium, Lutetium. And in sample 2 of the EDX tool, namely Aluminum, Silica, Iron, and Cobalt, and the results of field research that has been conducted using SEM-EDX and FTIR, it can be concluded that: The elemental composition of volcanic rock in Soputan volcano has Br, Si elements. , W, Au, Mo, Ca, Fe, Yb, Lu, Al, Co. As well as the type of rock minerals, basalt in sample 1 and sample 2 is andesite.